Curriculum Development and Dermatology Training - Jayadev Betkerur (Nepal Journal of Dermatology, Venereology & Leprology)
Curriculum is an integral part of any educational cycle. Curriculum development is a systematic process involving designing, implementing , evaluating and redesigning. There are different types of curriculums being practiced by institutions. Subject based curriculum is a widely used but competency based curriculum is the best. There is an urgent need to have relook at the existing curriculum as it is beset with many problems. The  faculty development (FD) is one factor affecting curriculum development. We need to identify the other issues and address them.